Narratives and Green Policy Implementation: A Case Study of the Sea Defence Project in Indonesia - Mohamad Sukarno; Dyah Mutiarin; Fauziah Saragih (INJECT (Interdisciplinary Journal of Communication), 2025)
The research aims to evaluate the implementation of the green policy concept in environmental management through a case study of sea fences in the Tangerang and Bekasi regions of Indonesia based on mass media. This project has received criticism from various parties because it is considered to cause many problems, especially in terms of Environmental Impact Analysis (EIA). The research method uses a qualitative approach with a descriptive approach on databases from the mass media. The data source was obtained from online news reporting on the sea fence case, which was then captured through the capture feature. Data analysis used Commissioned Qualitative Data Software (CAQDS) with the help of the NVivo 12plus device. The data analysis process uses coding techniques to identify narratives originating from three leading actors: the government, non-governmental organisations (NGOs), and the public. The results of the crosstab analysis show that government actors dominate the narrative (54%), followed by the public (25%) and NGOs (20%). The study results show that the dominance of the government's narrative is even ironically involved in the issuance of 263 problematic Building Rights (HGB) certificates in the project. This project impacts the destruction of marine ecosystems, loss of aquatic life habitat, coastal abrasion, and loss of livelihood of more than 3,800 fishermen, with economic losses of up to Rp24 billion. From the results of this study, the implementation of green policy in the sea fence project shows serious failures, especially in the aspects of supervision, transparency, and law enforcement. Therefore, firm action is needed from environmental violators to realise an innovative environment in a sustainable manner.